Soft Skills Integration at Moulay Ismail University: Insights from a Pre- and Post-Course Analysis - Harrif, Maroua; Azzouzi, Lamiae (International Journal of Linguistics and Translation Studies, 2025)
In Morocco, securing employment is a significant challenge, but maintaining that job and fostering a healthy work environment presents an even greater difficulty. Soft Skills are essential in addressing these challenges, providing the tools needed to navigate workplace dynamics and enhance professional relationships. Moreover, Soft Skills play a crucial role in university life, helping students manage academic pressures, collaborate effectively with peers, and engage in meaningful extracurricular activities. This study evaluates a carefully designed module at Moulay Ismail University to improve these skills among first-semester students. The module focused on critical areas such as university life, learning styles, research techniques, and information processing techniques, preparing students with the Soft Skills necessary for academic challenges and professional advancement. This study adheres to a quantitative approach using a pre-and post-course evaluation design. The research involved a detailed SPSS analysis. The analytical approach included generating descriptive statistics to summarize data, conducting pairwise comparisons to examine changes throughout the course, and applying multiple measures ANOVA to determine the statistical significance of improvements in soft skills. Results indicated a significant enhancement in students’ soft skills, confirming the effectiveness of the educational intervention. These findings highlight the importance of incorporating Soft Skills training into higher education curricula and support the continued inclusion of such training to improve student outcomes. Further research is suggested to explore the long-term effects of Soft Skills development on student success.